2017
DOI: 10.1177/1753495x17701320
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment and inflammation among pregnant women with gestational diabetes mellitus: A pilot study

Abstract: This pilot study was the first to demonstrate an association between childhood maltreatment history and inflammatory cytokine levels in pregnant women diagnosed with gestational diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…1 Findings are also in line with results from our previous cross-sectional study in which pregnant women with histories of childhood adversity displayed elevated proinflammatory cytokine levels. 5 Rates of childhood sexual abuse in this study (20%) were aligned with national averages, 32,33 and consistent with past evidence that childhood sexual abuse is uniquely dysregulating to stress-related biology in pregnancy. Specifically, studies have found that women with histories of childhood sexual abuse, with or without childhood physical abuse, displayed greater inflammation, 5 greater salivary cortisol 34 and greater hair cortisol 35 in pregnancy, particularly in the third trimester.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…1 Findings are also in line with results from our previous cross-sectional study in which pregnant women with histories of childhood adversity displayed elevated proinflammatory cytokine levels. 5 Rates of childhood sexual abuse in this study (20%) were aligned with national averages, 32,33 and consistent with past evidence that childhood sexual abuse is uniquely dysregulating to stress-related biology in pregnancy. Specifically, studies have found that women with histories of childhood sexual abuse, with or without childhood physical abuse, displayed greater inflammation, 5 greater salivary cortisol 34 and greater hair cortisol 35 in pregnancy, particularly in the third trimester.…”
Section: Discussionsupporting
confidence: 88%
“…According to the biological embedding model of early adversity, 1 experiences of childhood adversity program immune cells to have an exaggerated inflammatory response to stimuli and a decreased sensitivity to feedback from glucocorticoids, resulting in nonresolving inflammation and a "pro-inflammatory phenotype." Nonpregnant victims of childhood adversity display elevations in inflammatory cytokines (IL-6, IL-1b, TNF-a), [2][3][4] and there is some evidence, including work by our group, 5 that elevations in inflammation among victims of childhood adversity persist into pregnancy. [6][7][8] Prenatal depression is also highly prevalent among women who experienced childhood adversity 9 and is associated with elevated inflammation; higher depressive symptoms in pregnancy have been associated with higher C-reactive protein (CRP), 10 IL-6, 11 and IL-1b 12 in past research.…”
Section: Introductionmentioning
confidence: 87%
“…Childhood physical abuse, emotional abuse and emotional neglect were associated with elevated serum CRP across pregnancy (111). Women with gestational diabetes who had a history of childhood maltreatment had elevated IL-15 in pregnancy (112).…”
Section: Maternal Adverse Childhood Experiencesmentioning
confidence: 97%
“…7 Previously published data from this cohort show a significantly lower prevalence of SDB. 8 The differences in prevalence estimates of SDB in women with gestational diabetes mellitus (GDM) may be related to differences in racial and ethnic distribution, the technology used to diagnose SDB (in-laboratory polysomnography vs. in-home sleep monitors), and the definition of the condition.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, mechanisms underlying the association between OSA and metabolic outcomes such as GDM may be quite different in pregnancy than in the general population and are currently understudied. We have recently explored the potential role of the hypothalamic-pituitary-adrenal axis activation in this association and demonstrated that the cortisol awakening response was lower among pregnant women with OSA compared to those without, 8 after adjusting for depression and stress. We hypothesized that women with OSA may have elevated levels of circulating pro-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%